(3Jbhje GdCOhjI ajeG CTJgQ ef GdCYTGH hGdYbGbjQ hGdCZPjIs - (3EHQGgje Hf CHj SYjO Hf EHQGgje GdeZQHj GdYdGFj GdeJWHHs ((3eMeO Hf CHj GdbGSe GdeQGcTi s)
(3ChdgG (B:s
(3Ef Chd eG GaJJM Hg GdNWGH hCLd eG GHJOF Hg GdcJGH (B: (3GdJYXje dPcQ Gddg s
(3BNQgG (B:s
(3hjfJgi HPcQ GdCOhjI GdJi dgG GSeGf Ch KdGKI(B: (3MQa GdHGA ZdJGf (B: (3gh GdLOhGQ PcQ ai MQa GddLje s
(3cJHJ Ydi GdfSNI (B: (3JQJjH HYV aVdGA CWHGA GdYLes
(3hHNW BNQ (B: (3JCdja GdMcje jhMfG Hf HNJjThY hcd Pdc NWCs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B65 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B467s
Keywords: (3GdWHs